2021
DOI: 10.14233/ajchem.2021.23214
|View full text |Cite
|
Sign up to set email alerts
|

Spectral, Theoretical and Biological Studies of 3-((4-Mercaptophenyl)imino)- 1-phenylindolin-2-one Schiff Base and Its Organotellurium(IV) Complexes

Abstract: Schiff base ligand (3-((4-mercaptophenyl)imino)-1-phenylindolin-2-one) of 1-phenylindoline-2,3-dione and 4-aminothiophenol was synthesized by refluxing. Organotellurium(IV) complexes of type (RTeCl3.NPhIATP and R2TeCl2.NPhIATP, where R = 4-hydroxyphenyl, 4-methoxyphenyl and 3-methyl-4-hydroxyphenyl, NPhIATP = Schiff base ligand). The ligand and its organotellurium(IV) complexes (9a-f) were characterized by FT-IR, molar conductance, elemental analyses, UV-vis, mass, 1H & 13C NMR spectral studies. Geometry o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Therefore, we synthesized various group based organyltellurium complexes for comparing their pharmacological activities. The results of in vitro biological activities demonstrated that the organyltellurium (IV) complexes exhibit greater pharmacological efficacy than the Schiff base because of chelation, lipophilicity, redox activity, selective toxicity, DNA interaction, synergistic effects, enhanced cellular uptake and reactive oxygen species (ROS) generation 19,20,48‐55,60,61 . The results of the complexes regarding antimicrobial, antioxidant and anticancer activity differed, possibly because of different targeting mechanisms within cells that do not overlap.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we synthesized various group based organyltellurium complexes for comparing their pharmacological activities. The results of in vitro biological activities demonstrated that the organyltellurium (IV) complexes exhibit greater pharmacological efficacy than the Schiff base because of chelation, lipophilicity, redox activity, selective toxicity, DNA interaction, synergistic effects, enhanced cellular uptake and reactive oxygen species (ROS) generation 19,20,48‐55,60,61 . The results of the complexes regarding antimicrobial, antioxidant and anticancer activity differed, possibly because of different targeting mechanisms within cells that do not overlap.…”
Section: Resultsmentioning
confidence: 99%
“…4-Hydroxyphenyl tellurium (IV)trichloride, 3-methyl-4hydroxyphenyl tellurium (IV)trichloride, 4-methoxyphenyl tellurium (IV)trichloride, bis-(4-hydroxyphenyl) tellurium (IV)dichloride, bis-(3-methyl-4-hydroxyphenyl) tellurium (IV)dichloride and bis-(4-methoxyphenyl) tellurium (IV) dichloride were synthesized by treating tellurium tetrachloride with phenol, o-cresol, anisole in various molar ratios, following established procedures published in previous literature. [48][49][50][51][52][53] The synthetic pathway is illustrated in Scheme 2.…”
Section: Chemicals Methods and Instrumentationmentioning
confidence: 99%
See 3 more Smart Citations